Análise da diversidade genética entre linhagens de milho-pipoca - Rodrigues, Bruna (2015)
The genetic divergence among 15 popcorn lines was estimated using genomic DNA of seven plants of each genotype. For this estimate 40 microsatellite primers spread over all chromosomes were used. The PIC values (polymorphism information content) ranged from zero (Bnlg1297 and Umc2075) to 0,2061 (Mmc0181), with an average of 0,0869. A total of 128 polymorphic alleles were detected among the lines. The number of allele varied from 2 to 7 per locus with an average of 3,2 alleles per locus. The average heterozygosity ranged from 0,0176 to 0,2561.The rates of genetic dissimilarity were obtained based on the frequency of common alleles to contrasting lines. The matrix of dissimilarity allowed the performance of cluster analysis by the modified method of Tocher and the methods of nearest neighbor, furthest neighbor and UPGMA. The cophenetic correlation coefficients of each grouping methodology indicated that the UPGMA method was the most appropriated one to explain the varietal discrimination. The results obtained by the modified method Tocher showed the presence of four groups of lines, one of which consists of ten genotypes. The number of groups indicated by the UPGMA method was higher than that obtained under the Tocher method, showing practical advantages of UPGMA method. Despite some discrepancies, most of the clusters indicated by molecular analysis grouped materials of the same origin. The lines 1 and 4 derived from Colombiana and Zélia, respectively, showed great genetic dissimilarity in relation to the others. The lines 3 and 4 derived from IAC-125 and Zélia, respectively, expressed great genetic distance in the analyzed loci, making it possible on crosses intended to produce hybrids with the possibility of heterosis. Considering the studied loci, the large genetic distance between lines 3 and 4 allowed state them as parental genotypes to be used in the exploitation of heterosis.